EVALUASI KEBIJAKAN PERTANAHAN PENYELENGGARAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KABUPATEN LUMAJANG (Studi Kasus di Desa Tukum Kecamatan Tekung Kabupaten Lumajang) - Mayori, Nawang; Rosdiana, Weni (Universitas Negeri Surabaya, 2023)
The purpose of this activity is useful for accelerating the issuance of certificates. This study uses evaluation theory according to William.N Dunn which has 6 indicators, namely Effectiveness, Efficiency, Adequacy, Flattening, Responsiveness, and Accuracy. Thisstudy uses qualitative methods with a descriptive approach, data collection techniques with observation, interviews, and documentation. This study describes the evaluation of land policy implementation of complete systematic land registration in Tukum Village, Tekung District, Lumajang Regency. as follows: the assessment of the effectiveness of complete systematic land registration is related to the target of this PTSL which has not been certified from the amount of land in Tukum Village has not been effective. Efficiency is related to the issuance of land rights certificates that are still not maximized / incomplete in accordance with the time run. Adequacy is related to insufficient juridical data collection personnel. This alignment is related to the results of the registrant community in all hamlets in the Tukum Village area which has been evenly divided. Responsiveness is related to the large number of people who have not participated in this program. This accuracy is in accordance with the predetermined flow, which refers to and is guided by existing regulations. The suggestions given are: 1) Add juridical data collection officers to make the process accelerate 2). Update juridical data of land that has not been certified periodically 3) In terms of the complaintcarried out by the Land Office of Lumajang Regency and the Tukum Village Government, it was further improved 4). Provide understanding and awareness of landowners in order to prepare requirements and completeness of juridical data. Keywords : Government Policy, Legal Certainty of Land Rights, Complete Systematic Land Registration PTSL